Investigating Students’ Experiences on AI Integration in Chinese Listening Practices: A Study in Higher Education - Samad, Ita Sarmita; Mustarih, Nirdayanti; Akbar, Imam; Ismail, Ismail (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to explore students’ experiences in the use of Artificial Intelligence (AI) in the practice of listening to Chinese in the Chinese Language Education Study Program, Makassar State University. The research uses a qualitative approach with an exploratory descriptive design. The research participants totaled 55 students who were selected using the purposive sampling technique. Data was collected through open-ended questionnaires and semi-structured interviews to obtain a comprehensive picture of students’ experiences in using AI for Chinese listening practice. Data was analyzed using thematic analysis techniques which included the process of data familiarization, coding, theme identification, theme review, theme naming, and preparation of research results reports. The results showed that most students had positive experiences in using AI for Chinese listening exercises. AI is used for various learning activities, such as understanding pronunciation and intonation, enriching vocabulary, translating texts, and practicing understanding Chinese conversations. Most respondents also assessed that AI helps improve listening skills through flexible access, quick feedback, and wider self-learning opportunities. However, students consider that AI has not been able to replace the role of lecturers in providing contextual explanations, academic guidance, and more in-depth pedagogical interactions. This study concludes that AI has the potential to be an effective supporting medium in learning to listen to Chinese in universities if it is properly integrated with student-centered learning strategies.